Working Paper Part 1 : The Very First Pilgrimage - An Inspired Trajectory Out of Africa - Ian McIntosh (International Journal of Religious Tourism and Pilgrimage, 2022)
One hundred thousand years ago, give or take, the forebears of some of Australia’s First Nations—by some accounts as few as 150 people—left Africa on an immense journey. After some 2,000 generations, the passage through new and unfamiliar territories of these first modern human beings terminated in a supercontinent that included Australia, Papua, and Tasmania. By some estimates, no more than 150 people—the same number that had originally left Africa—made the final sea crossing that separates Indonesia and Australia. Research on such ancient migrations emphasises population growth, the ‘selfish gene,’ and the territorial imperative, as key drivers of mobility. This working paper speculates that the numinous was the equal to any other factor in migration, which is why this vast trek is called an inspired journey or the very first pilgrimage.